Employee's perceptions of information technologies and e-marketing in hotels in Serbia - Cimbaljević Marija; Blešić Ivana; Demirović Dunja F.; Milentijević Nikola (Marketing (Beograd. 1991), 2018)
For decades, the hotel industry has turned to technological innovations that raise its quality of services. In hotel industry, technologies redefined and re-formulated the service process in an innovative way. This paper aims to determine the status and level of knowledge of the currently available information technology (IT) systems, to determine the understanding of future IT opportunities and conditions in the hotel industry by employees, but also to gain understanding of IT requirements from their perspective in the near future. The paper also deals with issues related to the use of e-marketing in general, as well as in interaction with clients. The research has shown that hotel employees in Serbia have a positive attitude when it comes to the use and importance of information communication technologies. In addition, there is understanding for future IT opportunities and conditions in the hotel industry by employees. In the field of e-marketing, the results showed that it is possible to distinguish three important factors that influence the implementation of e-marketing practices in the hotel industry. This confirms the assumption that hotels in Serbia have accepted and that their business is to a certain extent based on e-marketing.